PENGARUH DEGRADASI HUTAN PADA POPULASI ANGGREK EPIFIT DAN KARAKTERISTIK TEMPAT TUMBUH ANGGREK DI KAWASAN GUNUNG AMBAWANG KABUPATEN KUBU RAYA - Irwanda, Hendra; Astiani, Dwi; Ekyastuti, Wiwik (Universitas Tanjungpura, 2018)
Indonesia is a country with the richest orchids spesies in the world. Forest degradation could be one of the factors that threatens the existence of orchids in the tropial forest. The purpose of this study was to search information on forest degradation impact on epiphytic orchid populations as well as the characteristics of the orchid site condition in the areal Ambawang Mountain Â Kubu Raya Regency. This study used survey method with stratified sampling technique on forest cover condition. Sampling area was 3 of a 40 m x 40 m, plot which divided into 4 sub plots of 20 m x 20 m. The results found 17 species of orchids with an 98 individual. There were 14 spesies orchid host trees with 130 number of trees, with three characters of bark on the host tree: rough, medium, and slightly smooth bark. Among 3 characters tree-bark type, the most orchid was found on Â rough-bark type. It also found differences in the number of population of orchid species at each level of canopy closure. Mute orchid spesies populations were found under therefore, the close forest cover condition. should be maintained. There for the forest canopy closure should be maintaind.Keywords: forest degradation, orchids spesies, site characteristics.